Tinjauan Yuridis Putusan Hakim Atas Perkara Pidana Persetubuhan Yang Dilakukan Oleh Anak : (Studi Putusan Nomor 32/Pid.Sus-Anak/2022/Pn Lahat) - Veronika Niken Larantukan; Debi F. Ng. Fallo; Orpa G. Manuain (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
Crimes against children that are rampant today are immoral crimes, namely sexual intercourse. In several cases of criminal acts of intercourse against children, there are often differences between the laws and regulations and the application of the law in the judge's decision. The research method used is Normative formulation of the problem as follows: (1) What is the basis of the judge's legal considerations in imposing punishment on child perpetrators of the crime of sexual intercourse in decision number: 32/Pid.Sus-Anak/2022/PN Lahat? (2) Is the judge's decision fair for child victims of the crime of sexual intercourse in decision number: 32/Pid.Sus-Anak/2022/PN Lahat?. The results showed that: (1) The basis of the judge's consideration includes juridical and non-juridical considerations. Juridical considerations include: 1) The indictment of the public prosecutor 2) Witness testimony 3) Statement of the defendant 4) Evidence 5) Articles charged. Non-juridical considerations, which are the basis for the judge's consideration, have 2 (two)categories, namely: Philosophical aspects include: a)The nature of the criminal offense (whether it is a serious or minor criminal offense), b)The threat of punishment for the criminal offense, the circumstances and atmosphere at the time of committing the criminal offense (which provide and alleviate), c)The defendant's personality whether he is a criminal who has been repeatedly convicted or a criminal for this one time only, unwritten law and the values that live in society, b) Taking into account the presence or absence of peace, guilt, the role of victims, c) Community factors, namely the environment where the law applies or is applied, d) Community factors, namely the environment where the law applies or is applied, e) Cultural factors, namely as a result of the work of creation and taste based on human spirit